2014
DOI: 10.1002/2013gl058340
|View full text |Cite
|
Sign up to set email alerts
|

Modeling shock waves generated by explosive volcanic eruptions

Abstract: Atmospheric shock waves induced by explosive volcanic eruptions can provide valuable information about eruption characteristics. Shock waves are manifested as pressure-density gradients that can be remotely observed with relatively little noise. Field measurements of expanding shock waves can be directly recorded by pressure transducers or imaged under the proper illumination and atmospheric conditions. In this paper, an open-ended shock tube was used to generate weak shock waves in the laboratory that are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Here the initial, large pressure front results from the liberation of pressurized gas at the beginning of the simulation. The same process has been shown to potentially generate supersonic blast waves, with initial Mach number > 6, at the beginning of explosions at several volcanoes [Marchetti et al, 2013;Medici et al, 2014]: the largely supersonic apparent velocity we found for our initial waves (Table 1) suggests that this could be the case also at Stromboli volcano. The different families of sustained waves can be tentatively attributed, based on their geometrical similitude with the modeled ones, to well-established types of jet noise, including (1) vortex ring noise, (2) predominantly forward directed noise from large shear layer structures, like toroidal or helical modes in the jet, (4) turbulent mixing noise, usually propagating sideward from the shear layer, (5) broadband shock-associated noise from supersonic jets, which is predominantly directed backward from a position about 5-7 jet diameters above the vent, and (6) screech noise, a tonal component due to a feedback of the shock-associated noise with the ground [Tam, 1995;Schulze and Sesterhenn, 2008].…”
Section: Jet Noise From Strombolian and Vulcanian Explosionssupporting
confidence: 72%
“…Here the initial, large pressure front results from the liberation of pressurized gas at the beginning of the simulation. The same process has been shown to potentially generate supersonic blast waves, with initial Mach number > 6, at the beginning of explosions at several volcanoes [Marchetti et al, 2013;Medici et al, 2014]: the largely supersonic apparent velocity we found for our initial waves (Table 1) suggests that this could be the case also at Stromboli volcano. The different families of sustained waves can be tentatively attributed, based on their geometrical similitude with the modeled ones, to well-established types of jet noise, including (1) vortex ring noise, (2) predominantly forward directed noise from large shear layer structures, like toroidal or helical modes in the jet, (4) turbulent mixing noise, usually propagating sideward from the shear layer, (5) broadband shock-associated noise from supersonic jets, which is predominantly directed backward from a position about 5-7 jet diameters above the vent, and (6) screech noise, a tonal component due to a feedback of the shock-associated noise with the ground [Tam, 1995;Schulze and Sesterhenn, 2008].…”
Section: Jet Noise From Strombolian and Vulcanian Explosionssupporting
confidence: 72%
“…For all three eruptions, CRF was registered in synchrony with strong acoustic and seismic signals, suggesting that (as in our experiments) vent discharge result from overpressured conditions at the vents (Figure ). Assuming simple geometric spreading, the pressure at the vent, P v , can be estimated from pressure anomalies detected from afar (Medici et al, ): Pv=Pmrm/rv …”
Section: Field Observationsmentioning
confidence: 99%
“…Because infrasound is typically sourced from within the conduit, line‐of‐sight conditions are rarely possible. Acoustic waves are modified as they interact with crater morphology and cone structure (Lacanna & Ripepe, ; Medici et al, ) and by atmospheric conditions, including wind direction and speed (Johnson & Ripepe, ). Thus, the pressure ratios computed here likely underestimate the true overpressures at the vent.…”
Section: Field Observationsmentioning
confidence: 99%
“…Visual observations of wavefronts above erupting vents imply near‐source shock wave formation (Ishihara, ; Yokoo & Ishihara, ), but these waves do not necessarily indicate supersonic sources (Genco et al, ). Nonlinear propagation has been proposed as a possible explanation for asymmetric infrasound waveforms, which are commonly observed at volcanoes worldwide (e.g., Anderson et al, ; Fee et al, ; Marchetti et al, ; Matoza et al, ; Medici et al, ). However, this phenomenon can alternatively be explained with linear propagation and crater rim diffraction (Kim & Lees, ) or fluid flow at the source (Brogi et al, ).…”
Section: Introductionmentioning
confidence: 99%